INDONESIA’S PUBLIC DIPLOMACY TOWARDS MALAYSIA - Iva - Rachmawati (Department of International Relations, Universitas Andalas, 2018)
Indonesian public diplomacy has been understood as an effort to attach a certain image like a moderate, democratic and progressive image. Nevertheless, the image is not always present in bridging Malaysian bilateral relations. In Malaysia Malaysia's bilateral relations practice, public diplomacy reveals itself in a different face. This article places public diplomacy not only as an effort to maintain the image in rationalists view, but public diplomacy as an effort to maintain relationships through shared identity. Through Indonesian diplomatic studies on Malaysia's three main issues over the past 15 years, it was found that public diplomacy was present as an effort to maintain relations through the shared identity as the Bangsa Serumpun (One Kin) or known as Kinship. Although Malaysia social economic context has changed, Indonesia still believes that the obligation to place the stability of relationships is a priority. Self-refrain and encouraging public dissemination become the practices of Indonesian public diplomacy towards Malaysia. Through qualitative methods, Indonesian policy documentation studies of three major bilateral issues found that Kinship is still the main reference for Indonesia in maintaining bilateral relations although it’s practiced differently. Key Words: Public Diplomacy, Shared Identity, Kinship.